Development of Learner Activity Sheets (LKPD) Based on Cognitive Structure and Metacognition Ability - Anita, Anita; Sukadi, Eti; Liliawaty, Winny; Azmar, Azmar (Universitas Islam Negeri (UIN) Mataram, 2024)
This research was conducted to develop learner activity sheets (LKPD) based on cognitive structures and metacognition skills. The LKPD is aimed at Class XI students of MA Walisongo Pontianak which is a boarding school. LKPD is prepared to improve the cognitive structure ability of students in the aspects of comparative thinking structure, symbolic representation structure, and logical reasoning structure and metacognition ability of students in the aspects of planning, monitoring, reflection. LKPD material is adjusted to the competency standards, namely applying the laws of static fluid, designing and conducting experiments that utilise the properties of static fluid. The stages of this development research are up to the analysis and design stages which are part of the ADDIE design research design.